Text as tape: On the voice in the late prose of Friederike Mayröcker - Elander, Astrid (Orbis litterarum, 2025)
For a text to have a voice means to be caught in a paradox: the text obviously does not speak, so what is that tone rising from the pages? Taking hold of a striking ambivalence, this essay examines the relationship between text and voice in the late prose of Austrian poet Friederike Mayröcker. After analyzing the texts using the voice as a poetological category, a way for the text to be, it proceeds by anchoring the outcome in relation partly to a contemporary philosophical discourse, partly to media‐historical development, which in turn calls for a revaluation of the qualities usually associated either with text or voice. The voice is thus investigated not only as a theme or a question of mediation, but also as a historically variable condition that gives rise to a certain subjectivity, with a particular way of narrating. Throughout the essay, the tape recorder is suggested as a suiting metaphor for the prose, presenting the paradox between text and voice at its core. The aim is also to show how Mayröcker uses this paradox to challenge the notion of the voice as an immediate expression of the subject.